2006
DOI: 10.1038/sj.onc.1209926
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18 is a critical factor for vascular endothelial growth factor-enhanced migration in human gastric cancer cell lines

Abstract: Cell migration and angiogenesis are key steps in tumor metastasis. However, the mechanism of migration regulated by vascular endothelial growth factor (VEGF), a potent regulator of angiogenesis, is not completely understood. This study examined the relationship between VEGF and migration, along with the mechanism involved in the VEGF-regulated migration of human gastric cancer cells. The level of cell migration was increased by recombinant human (rh)VEGF-165 in the VEGF receptor-2-expressing SNU-601 cells. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 20 publications
(21 reference statements)
3
60
1
Order By: Relevance
“…1A shows the expression of VEGFR-3 on SNU-601 cells. It was previously reported that VEGFR-2 is strongly expressed on SNU-601 cells (3). Exogenous VEGF-D (50 ng/ml) significantly enhanced cell migration in both a dose-and time-dependent manner (Fig.…”
Section: Il-18 Plays An Important Role In Vegf-d-enhanced Migrationmentioning
confidence: 51%
See 1 more Smart Citation
“…1A shows the expression of VEGFR-3 on SNU-601 cells. It was previously reported that VEGFR-2 is strongly expressed on SNU-601 cells (3). Exogenous VEGF-D (50 ng/ml) significantly enhanced cell migration in both a dose-and time-dependent manner (Fig.…”
Section: Il-18 Plays An Important Role In Vegf-d-enhanced Migrationmentioning
confidence: 51%
“…This indicates that the regulation of the IL-18 secretion process is critical for tumor progression. In our previous study, we reported that vascular endothelial growth factor (VEGF) 3 165 enhanced IL-18 production in human gastric cancer cells, resulting in increased IL-18-mediated migration (3). VEGF, a member of the plateletderived growth factor family, is known as the most potent proangiogenic factor.…”
mentioning
confidence: 99%
“…Inhibiting IL-18 markedly reduced the level of Vascular endothelial growth factor (VEGF)-enhanced migration, and IL-18 increases cell migration directly through filamentous-actin polymerization and tensin down regulation (Kim et al, 2007). Human IL-18 induces micro vascular endothelial cell (HMVEC) migration.…”
Section: Il-18 Enhances Angiogenesismentioning
confidence: 99%
“…However, previous studies have shown that IL-18 also exerts favorable effects on tumor progression (2-4). mutual stimulation between this cytokine and vascular endothelial growth factor (20,21). Some studies have also suggested that IL-18 stimulates migration of tumor cells in a matrix metalloproteinase-dependent manner (22,23).…”
Section: Discussionmentioning
confidence: 98%